Percepción del clima escolar y violencia en estudiantes de quinto grado de la Institución Educativa Noroccidental sede Muvdi (2016)
This research project was carried out in a public school in Soledad, Atlántico in the north coast f Colombia. For the present study a sample of 24 students were asked to participate in the application of some data collection methods such as an interview, a focus group, and an interview in order to determine what the perception student population had about the school climate. In short, students affirmed that school climate is neutral. However, students claim that there is much evidence of physical and verbal violence, especially among male students. Despite of the fact that students confirmed that there is violence in the school, they showed a great level of satisfaction with the interpersonal relationships among adults in the school.